"Notorious RBG": A conversation with United States Supreme Court Justice Ruth Bader Ginsburg. (27th April 2021) - Rubio-Marín, Ruth
Abstract: On February 2, 2016, Prof. Ruth Rubio-Marín, Chair of Constitutional and Comparative Public Law at the European University Institute (EUI), interviewed the U.S. Supreme Court Associate Justice Ruth Bader Ginsburg. The interview took place in the framework of the European University Institute's annual Ursula Hirschmann Lecture, a space dedicated to stimulate research and thinking which links ideas about Europe and the study of gender. Justice Ruth Bader Ginsburg engaged in a conversation that tackled her whole persona, without making rigid divides between the professional and the personal. Deep legal analysis, personal anecdotes, and invaluable advice for future researchers and lawyers intertwine in the interview, which sheds light on important dimensions of equality law.